Peran Brand Love Memediasi Pengaruh Customer Experience terhadap Repurchase Intention pada Restoran Blue Ocean Seafood Kedonganan (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to analyze the influence of customer experience on brand love and repurchase intention, as well as evaluate the role of brand love as a mediating variable in the relationship. The focus of the research was directed at local tourists who had made purchases at Blue Ocean Seafood Restaurant. A sample of 100 respondents was obtained through a non-probability sampling method with a purposive sampling technique, which was selected based on consumers' direct experience of restaurant services. A quantitative approach is used in this study, with path analysis techniques as a data analysis method to test the relationship between variables. The results of the study show that customer experience has a positive and significant influence on repurchase intention, which indicates that a good customer experience encourages the intention to make a repurchase. In addition, customer experience also has a positive and significant effect on brand love, showing that a pleasant experience can increase love for the brand. Brand love itself has been proven to have a positive and significant effect on repurchase intention, strengthening the emotional role of consumers in repurchase decisions. Furthermore, brand love has been shown to be able to partially mediate the influence of customer experience on repurchase intention, which means that part of the influence of customer experience on repurchase intention occurs through love for the brand. These findings provide strategic implications for restaurant managers in designing a memorable customer experience to build loyalty and increase repurchase intent through strengthening brand love.